الإشارات القرآنية إلى الزراعة دراسة تحليليّة في ضوء مقاصد الشريعة - Mohamed Hamadikinane Maiga (Al-Zahra: Journal for Islamic and Arabic Studies)
This study aims to demonstrate the relationship between man and this earth on which we live, through the Qur’anic references to agriculture, which indicate that the land is the origin of man and his settlement. Allah Almighty made it a firm foundation for man to rest on without it swaying from them. And he (Allah S.W) has prepared this earth for human life, and placed in it all the requirements of life; Water, oxygen, trees, plants, minerals, humanized animals, etc. He (Allah S.W) created all that for man and subjected it to him to establish his worldly life for his life in the hereafter, within the framework of the responsibility of succession in the earth, and in the light of Maqàsid Al-Shariah. The researcher followed the descriptive analytical approach to reveal this relationship and how to exploit it to achieve human well-being in this life, and happiness in the hereafter. The study concluded that the earth is the only planet that Allah has prepared for human life. Hence, man must invest this land in agriculture to ensure his livelihood and well-being, and to engage in planning, organization and justice in order to ensure sustainable development.